2004
DOI: 10.1021/jf049517a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Commercial Anthocyanin-Rich Extracts on Colonic Cancer and Nontumorigenic Colonic Cell Growth

Abstract: Commercially prepared grape (Vitis vinifera), bilberry (Vaccinium myrtillus L.), and chokeberry (Aronia meloncarpa E.) anthocyanin-rich extracts (AREs) were investigated for their potential chemopreventive activity against colon cancer. The growth of colon-cancer-derived HT-29 and nontumorigenic colonic NCM460 cells exposed to semipurified AREs (10-75 microg of monomeric anthocyanin/mL) was monitored for up to 72 h using a sulforhodamine B assay. All extracts inhibited the growth of HT-29 cells, with chokeberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
198
5
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(218 citation statements)
references
References 33 publications
11
198
5
4
Order By: Relevance
“…Suppression of survival by 50% of the HT29 cell line by 25 lg of cyanidin 3-glucoside/mL after a 48-h exposure to anthocyanins from chokeberry, with no effect on the growth of normal non-transformed colon epithelial cells (NCM460), was observed. 10 The effects of bilberry extract anthocyanins on cervical cancer HeLa cells showed that the inhibitory rate increased after 48 h of treatment. 45 …”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of survival by 50% of the HT29 cell line by 25 lg of cyanidin 3-glucoside/mL after a 48-h exposure to anthocyanins from chokeberry, with no effect on the growth of normal non-transformed colon epithelial cells (NCM460), was observed. 10 The effects of bilberry extract anthocyanins on cervical cancer HeLa cells showed that the inhibitory rate increased after 48 h of treatment. 45 …”
Section: Antioxidant Activitymentioning
confidence: 99%
“…6,7 These berries, because of their high content in anthocyanins, are being studied also for their ability to protect against oral, 8 colon, 9,10 breast, 8 and prostate 11,12 cancer. The objectives of this study were (1) to determine the contents of total flavonoids, procyanidins, anthocyanins, and polyphenols of chokeberry extracts obtained from three cultivars and to characterize their anthocyanin fraction by high-performance liquid chromatography (HPLC) analysis, (2) to measure and compare the antioxidant activity using three different single electron transfer (SET)-based assays [2,2 0 -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric reducing antioxidant power (FRAP), and cupric ion reducing antioxidant capacity (CUPRAC)], one hydrogen atom transfer (HAT)-based method (oxygen radical absorbance capacity [ORAC]), and the H 2 O 2 scavenging potential (HPS) assay, and (3) to evaluate the cytotoxic action and the pro-oxidative effect of the anthocyanin fraction on the HeLa tumor cervical cell line.…”
Section: Introduction Tmentioning
confidence: 99%
“…They have been recognized as health-promoting functional food ingredients due to their antioxidant activity (Nam et al 2006;Philpott et al 2006;Satue-Gracia et al 1997), which has been reported to reduce the risk of coronary heart disease (Stocker and O'Halloran 2004;Waterhouse 1995). Anthocyanins are also known to have anti-cancer (Hyun and Chung 2004;Kamei et al 1995;Zhao et al 2004), hypoglycemic (Tsuda et al 2003), and anti-inflammatory effects (Tsuda et al 2002) and have been used in the treatment of various circulatory disorders (Bettini et al 1985). Furthermore, these functions provide synergic effects with various nutrients in vivo, so their nutritional values are of great interest recently.…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins, a group of reddish or purple flavonoids, are reported to be the primary pigments in these rice varieties (Abdel-Aal & Huel, 1999;Mazza & Gao, 2005;Moreno et al, 2005). Anthocyanins have been recognized as health-promoting functional food ingredients due to their antioxidant activity (Nam et al, 2006;Philpott et al, 2006), anticancer (Hyun & Chung, 2004;Zhao et al, 2004), and anti-inflammatory effects (Tsuda et al, 2002), and these functions provide synergic effects with various nutrients in vivo. At present, red rice is commonly used as a food colorant in bread, ice cream, and liquor (Yoshinaga, 1986).…”
mentioning
confidence: 99%